Análise espacial da mortalidade neonatal no Vale do Paraíba, 1999 a 2001 Spatial analysis of neonatal mortality in Paraíba Valley, Southeastern Brazil, 1999 to 2001 - Luiz Fernando C Nascimento; Getulio T Batista; Nelson W Dias; Celso S Catelani; Daniela Becker; Luciana Rodrigues (Universidade de São Paulo, 2007)
OBJETIVO: Analisar os padrões de distribuição espacial da mortalidade neonatal. MÉTODOS: Estudo ecológico e exploratório, utilizando técnicas de análise espacial dos dados de mortalidade neonatal no Vale do Paraíba paulista, nos anos 1999-2001. A análise estatística espacial utilizou uma base de dados georreferenciados de 35 municípios e rotinas de estatística espacial. Os dados de mortalidade foram obtidos na Secretaria de Estado da Saúde de São Paulo. As variáveis estudadas foram os coeficientes de mortalidade neonatal precoce, tardia e total, e o Índice de Desenvolvimento Humano relativos ao ano de 2000. Para avaliação da dependência espacial foram utilizados os coeficientes de autocorrelação de Moran global e o Índice de Moran local e analisadas as correlações entre as variáveis. RESULTADOS: Foram registrados 111.574 nascidos vivos, com 1.149 óbitos no período neonatal precoce (10,29/1.000 nascidos vivos), 285 no neonatal tardio (2,55/1.000 nascidos vivos) totalizando 1.434 óbitos no período neonatal (12,85/1.000 nascidos vivos). Os coeficientes de Moran (global) mostraram significância estatística (p<0,05) para as mortalidades neonatal precoce e neonatal total. Os índices locais mostraram agrupamentos de municípios onde ocorre dependência espacial na ocorrência das mortalidades precoce e total. CONCLUSÕES: A análise espacial permitiu identificar aglomerado espacial no médio Vale do Paraíba tanto para a mortalidade neonatal precoce como para a neonatal total. OBJECTIVE: To assess the spatial distribution of neonatal mortality. METHODS: An ecological and exploratory study using a spatial distribution of mortality data approach was carried out in the Paraiba Valley, Southeastern Brazil, from 1999-2001. Spatial analysis was conducted in a georeference database for 35 cities in the region and routines of spatial statistics. Mortality data were obtained from the State of São Paulo Health Department. The following variables were analyzed in this study: early, late and total neonatal mortality rates; and Human Development Index (HDI) values per city in 2000. Spatial dependency was measured using global Moran's Coefficients and local Moran's Index. A correlation analysis between variables was also conducted. RESULTS: There were 111,574 newborns with 1,149 deaths in the early neonatal period (10.29/1,000 newborns), 285 in the late neonatal period (2.5/1,000 newborns) totalizing 1,434 neonatal deaths (12.85/1,000 newborns). Estimated global Moran's coefficients showed statistical significance (p<005) for early and total neonatal mortality. Local Moran's index values showed clusters of municipalities for early and total neonatal mortalities rates. CONCLUSIONS: Spatial analysis allowed to identifying spatial clusters for early and total neonatal mortality rates in the central area of the Paraiba Valley.